Association between direct interpersonal involvement with a dying family member and discussions regarding advance care planning among Japanese older adults. Issue 2 (14th December 2020) - Miyashita, Jun; Hayashi, Shinu; Yamamoto, Yosuke
Abstract : Aim: There is growing recognition of the need to hold advance care planning discussions. Older adults who have direct interpersonal involvement with dying family members might begin to consider their own end‐of‐life care. This study examined the associations between experiences of being with a dying family member and advance care planning discussions among Japanese older adults. Methods: This study examined data from a previous self‐administered questionnaire survey carried out among outpatients aged ≥65 years. All participants were visitors of a community hospital in Japan, with data being collected over a 1‐week period in July 2016. The main exposure was experiences of being with dying family members, while the outcome was advance care planning discussions with the family members and/or their physician. We analyzed the associations between experiences of being with dying family members and advance care planning discussions through log‐binomial regression models adjusted for possible sociodemographic confounders. Results: Of the 302 respondents included for analysis, 96 (32%) had experiences of being with dying family members, while 179 (59%) held advance care planning discussions. Respondents with said experiences were more likely to have discussions than those without experiences (fully adjusted prevalence ratio 1.31, 95% confidence interval 1.04–1.65). Subgroup analyses showed no significant interaction effects between experiences of being with dying family members and the covariates. Conclusions: Direct interpersonal involvement with dying family members might facilitate advance care planning discussions among Japanese older adults. Our results should help healthcare providers recognize individuals who are unlikely to have discussions. Geriatr Gerontol Int 2021; 21: 197–202 .